Rockweed (Ascophyllum nodosum) in Breiðafjörður, Iceland: Effects of environmental factors on biomass and plant height - Lilja Gunnarsdóttir 1990- (2018)
During the Last Glacial Maximum (LGM) ice covered all rocky shores in eastern N-America while on the shores of Europe ice reached south of Ireland where rocky shores were found south of the glacier. After the LGM, rocky shores ecosystem development along European coasts was influenced mainly by movement of the littoral species in the wake of receding ice, while rocky shores of Iceland and NE-America were most likely colonized from N-Europe. Climate change likely facilitates new introductions of southerly species and removal of northern species which may change rocky shore ecosystems in Iceland. Rockweed (Ascophyllum nodosum) has been harvested commercially in Breiðafjörður since 1975. Plans to increase harvesting create need for information on growth, biomass and distribution. The aim of this study was to determine effects of physical factors on plant size and biomass. Biomass and plant height were determined at 37 stations in Breiðafjörður. Mean biomass of rockweed in Breiðafjörður was 13.5 kg m-2. Biomass and plant height were significantly related to location. Biomass increased from southwest towards northeast in the fjord. Plant height was inversely related to exposure. The relationship between location, rockweed biomass and plant height is likely explained by different local conditions. Mean biomass of rockweed is high in Breiðafjörður, which is close to the northern distribution limits, where rockweed has a relatively slow growth rate and lacks efficient grazers. Grjót- og klettafjörur á austurströndum N-Ameríku og vesturströndum Evrópu voru þaktar ís á hámarki síðasta kuldaskeiðs ísaldar, fyrir utan svæði suður af Írlandi í Evrópu. Myndun vistkerfa grjót- og klettafjara í fjörum Evrópu eftir kuldaskeiðið var að mestu leyti vegna fjörutegunda sem fylgdu í kjölfar hörfandi ísaldarjökulsins. Landnám fjörutegunda í grjót- og klettafjörur Íslands var hins vegar líklegast frá N-Evrópu. Líklega munu loftlagsbreytingar auðvelda innleiðingu nýrra suðrænna tegunda og brottflutning norrænna tegunda sem gæti breytt ...